Clarification of Pineapple Juice Following Egg Albumin Pretreatment: Investigation of Membrane Fouling Dynamics Using Hermia’s Empirical Models - Samreen (Food Science and Agriculture: Research Highlights Vol. 1, 2025)
Pineapple (Ananas comosus L., Merril) is a tropical non-citrus fruit, mainly because of its attractive aroma, refreshing flavour and Brix/acid ratio. This juice has been used in fruit-based beverages individually, in the form of a mixture or combined with other fruit juices. The present study investigated membrane fouling during the clarification of pineapple juice after pretreatment with egg albumin. Pineapple (Ananas comosus L., Merril) is the most popular tropical non-citrus fruit, mainly because of their attractive aroma, refreshing flavour and Brix/acid ratio. The research was focused on the membrane clarification of pineapple juice following pretreatment. Pretreatment of pineapple juice was performed using egg albumin with different concentrations and observed that 2 g/L concentration gave effective removal of colloidal substances of pineapple juice. The membrane processing of pineapple juice was performed with all different pore sizes, pressures, and flow rates and the coefficient of determination (R2) values were analysed. Hermia’s empirical models were applied to evaluate the fouling phenomena in the microfiltration (MF) and ultrafiltration (UF) of pineapple juice. The flux data was fitted into existing fouling models to elucidate the fouling mechanisms during membrane processing. The coefficient of determination (R²) values for the gel layer model ranged from 0.829 to 0.957 for the 0.2 µm pore size membrane when filtering pineapple juice. In the Microfiltration (MF) membrane, the data revealed that IPB was predominant, as the pore size of the membrane is larger than Ultrafiltration (UF). The coefficient of determination (R2) values for the gel layer model were in the range of 0.829 to 0.957 for 0.2 µm pore size membrane when pineapple juice was filtered. R2 values suggested intermediate pore blocking followed by gel layer formation.